Implementation of Green Marketing Mix at The Body Shop: A Marketing Strategy to Increase Consumer Satisfaction and Brand Loyalty - Yasari, Niluh Komang Kusuma; Agustin, Resty; Winarno, Agung; Rahayu, Wening Patmi (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze The Body Shop's implementation of Green Marketing Mix elements in the Indonesian market in the period 2023-2024, as well as its influence on consumer satisfaction and brand loyalty. Given the intensive competition in the cosmetics and body care sector, The Body Shop's ability to maintain differentiation through ethical values and sustainability is crucial. This research uses the Systematic Literature Review (SLR) method to synthesize findings from relevant studies on the Green Marketing Mix, consumer satisfaction, and brand loyalty, particularly in the context of the cosmetics industry and The Body Shop's business practices. The main focus of the analysis is on the four core elements of the Marketing Mix (Product, Price, Place, and Promotion) with a sustainability (Green) perspective. The results of the study are expected to provide strategic insights to The Body Shop in optimizing the Green Marketing Mix to increase consumer satisfaction and strengthen brand loyalty in the Indonesian market, as well as provide an academic contribution in understanding the implementation of green marketing in the cosmetics industry.